COX-2 Signaling and Cancer: New Players in Old Arena - Misra, Shashank; Sharma, Kulbhushan (Current Drug Targets, 2014)
Cancer is a leading cause of death worldwide. The expression of COX-2 and prostaglandins has not only been associated with various types of cancer but is also directly proportional to their aggressiveness including metastasis. Thus, inhibition of COX-2 activity has been one of the preferred targets for cancer reduction. Broad spectrum inhibition of all forms of COX (using NSAIDs) is associated with various side effects ranging from gastric ulceration to renal problems. Even specific COX-2 inhibitors (COXIBs) are associated with side effects like myocardial infarction. Alternative strategies including siRNA technology are also not very victorious due to their off-target associated problems. Thus, there is an urgent need for the development of strategies where COX-2 activity may be reduced without inducing any side effects. One of the approaches for designing novel inhibitors may be to target various molecules downstream of COX-2. In this review, we have tried to cover the basic biology of COX-2 and its association with different types of cancer. Various generations of COX-2 inhibitors have been covered with their merits and demerits. Possible exploitation of novel targets like EP receptors, mPGES and various other downstream molecules which can be utilized for a better COX-2 signaling inhibition and thus efficient cancer reduction with minimal side effects has been discussed.
Keywords: NSAIDs